2011
DOI: 10.1177/1545968310390223
|View full text |Cite
|
Sign up to set email alerts
|

Dose–Response Study of Mobilisation and Tactile Stimulation Therapy for the Upper Extremity Early After Stroke

Abstract: The authors were not able to deliver a maximum dose of 120 minutes of daily therapy each day. The mean daily dose of MTS feasible for subsequent evaluation is between 37 and 66 minutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 30 publications
0
22
0
1
Order By: Relevance
“…666,728,729,[731][732][733] A variety of interventions have been the focus of ≥1 studies but have not yet been shown to be consistently beneficial for upper limb motor rehabilitation. These include somatosensory stimulation [734][735][736][737][738] and noninvasive brain stimulation (transcranial magnetic stimulation or tDCS) in combination with upper extremity exercise therapy, [739][740][741][742][743][744][745][746] interventions targeting motor apraxia, 458 and manual therapy approaches such as stretching, passive exercise, and mobilization, 748 although these approaches are a routine part of practice for individuals with more severely affected upper extremities to prevent contractures and to manage spasticity.…”
Section: Iib Bmentioning
confidence: 99%
“…666,728,729,[731][732][733] A variety of interventions have been the focus of ≥1 studies but have not yet been shown to be consistently beneficial for upper limb motor rehabilitation. These include somatosensory stimulation [734][735][736][737][738] and noninvasive brain stimulation (transcranial magnetic stimulation or tDCS) in combination with upper extremity exercise therapy, [739][740][741][742][743][744][745][746] interventions targeting motor apraxia, 458 and manual therapy approaches such as stretching, passive exercise, and mobilization, 748 although these approaches are a routine part of practice for individuals with more severely affected upper extremities to prevent contractures and to manage spasticity.…”
Section: Iib Bmentioning
confidence: 99%
“…Previous studies have mainly used dose-ranging designs with pre-specified doses with parallel groups [35] or intervention crossover [36]. The authors are only aware of one previous dose-finding study of a rehabilitation intervention, but a different design was used to that reported here [37].…”
Section: Discussionmentioning
confidence: 99%
“…MTS involves hands-on sensorimotor stimulation to the forearm and hand. 13 Physiotherapeutic techniques, such as passive and accessory movements, cutaneous stimulation and proprioceptive feedback, active-assisted and active movement, and facilitation or guiding of functional patterns of movement, are individual components of MTS and are delivered in an appropriate combination. The selection of such an appropriate combination is based on the clinical reasoning of a skilled therapist according to patient presentation.…”
mentioning
confidence: 99%
“…14 A subsequent randomized, single-blind, phase I dose-modeling trial of MTS recommended a dose of 60 minutes daily in preference to a dose of 30 minutes, 120 minutes, or no MTS, in addition to a program of routine therapy. 13 The potential effect of MTS appears to be one of priming 13 the sensorimotor system for activity through sensory stimulation; mobilization of joints, soft tissues, and body segments provides proprioceptive stimulation, and cutaneous stimulation provides tactile, mechanical (pressure, stretch), and proprioceptive stimulation through mechanoreceptors in the glabrous (nonhairy) skin of the hand. 15 Thus, the rationale is one of priming and/or augmenting activity in the motor execution system to facilitate the voluntary contraction of paretic muscle.…”
mentioning
confidence: 99%
See 1 more Smart Citation